Mechanism and experimental validation of a thermochemical energy conversion process by utilization of biogas chemical energy. (15th June 2020) - Su, Bosheng; Han, Wei; He, Hongzhou; Jin, Hongguang; Yang, Shaohui; Zhang, Xiaodong
Highlights: Mechanism of a thermochemical energy conversion process is revealed. Parameter selection rule is given from a global perspective. A criterion is obtained with regard to both biogas and solar energy use. The mechanism is preliminary validated by the key process experiment. Abstract: Biogas and solar energy are two types of renewable energy which are always utilized in distributed energy systems in a simple superposition way. The physical thermal energy in biogas is used in a cascaded way in the conventional designs; however, the exergy destruction reaches maximum in the biogas direct combustion. A thermochemical energy conversion process integrating solar thermal energy and biogas steam reforming can utilize both chemical and physical energy efficiently. Based on the energy and exergy analysis approach, the reasons for the performance improvement of this process are clarified by an analytic expression in the mechanism study. Based on this, a new criterion is developed to evaluate the process from a global perspective. The optimal design combined with carbon deposition analysis was conducted, and the optimum temperature for the critical steam-to-carbon ratio is 704 °C, and the performance improvement can be achieved by 4.55%. In addition, the key process of the biogas components conversion is experimentally researched. The results in the mechanism study and the results based on the key process experiment were compared, and the error analysis demonstrates that the proposed mechanism has been validated and could be accepted with confidence. The mechanism researches provide a guide for optimal design of the energy systems consisting of the solar-driven biogas reforming process or other fuel conversion processes.